2017
DOI: 10.1039/c7ra04903j
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of USPIOs for T1-weighted MR molecular imaging of tumor receptors

Abstract: USPIOs having a superior T1 contrast effect could only be used for T2-weighted, but not for T1-weighted MR tumor receptor imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
(64 reference statements)
2
9
1
Order By: Relevance
“…These results indicated that in contrast with traditional iron oxide nanoparticles that are negative T 2 contrast agents, USPIO nanoparticles (<5 nm) can function as simultaneous positive and negative MRI contrast agents. This was in accordance with the findings of other groups [2, 24, 36, 38], which could be attributed to the relatively larger number of Fe 3+ with 5 unpaired electrons over the surface of smaller USPIO nanoparticles with larger surface area [40]. In addition, as the concentration of USPIO nanoparticles increased, there was an enhancement of the longitudinal and transversal relaxation rate, which suggested that they could be used in dynamic enhancement MRI, such as perfusion and permeability.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results indicated that in contrast with traditional iron oxide nanoparticles that are negative T 2 contrast agents, USPIO nanoparticles (<5 nm) can function as simultaneous positive and negative MRI contrast agents. This was in accordance with the findings of other groups [2, 24, 36, 38], which could be attributed to the relatively larger number of Fe 3+ with 5 unpaired electrons over the surface of smaller USPIO nanoparticles with larger surface area [40]. In addition, as the concentration of USPIO nanoparticles increased, there was an enhancement of the longitudinal and transversal relaxation rate, which suggested that they could be used in dynamic enhancement MRI, such as perfusion and permeability.…”
Section: Discussionsupporting
confidence: 94%
“…The core diameter of USPIO nanoparticles was <4.20 nm (3.26 ± 0.87 nm) as shown in TEM image (Figure 1(a)) and core size distribution analysis (Figure 1(b)), indicating significant potential as a positive contrast agent [29, 3840]. It was found simultaneously from T 1 -weighted and T 2 -weighted images and signals of the phantom in Figures 2(a) and 2(b) a positive enhancement of the T 1 -weighted MR signal and a negative enhancement of the T 2 -weighted MR signal as iron concentration increasing.…”
Section: Resultsmentioning
confidence: 99%
“…First, single biomarkers might hinder detection efficiency of existing HCC molecular probes due to tumor heterogeneity. Additionally, iron oxide nanoparticles used in the majority of current HCC imaging studies are utilized as negative (T2) contrast agents, which could result in inaccurate diagnosis[ 25 , 26 ]. However, opportunities to improve these probes also exist.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles exhibit size-dependent magnetic properties. Ultra-small superparamagnetic iron oxide (USPIO) nanoparticles of a small core size (approximately 5 nm) are suggested as optimal positive (T1) contrast agents that enhance T1 and suppress T2 signals induced by reductions in volume of magnetic anisotropy, surface spin disorder, and exposure of iron ions with unpaired electrons[ 26 - 30 ]. Additionally, slow phagocytosis of USPIO nanoparticles by macrophages makes them ideal for liver-tumor MRI[ 31 - 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, contrast agents can be divided into two categories depending on the effect they have on MRI. T 1 contrast agents shorten longitudinal relaxation times, generating bright signals [11][12][13][14][15], whereas T 2 contrast agents shorten transverse relaxation times, generating dark signals [16,17]. Even though T 1 contrast agents, such as Gd-DTPA (gadolinium diethylenetriaminepentacetate), are highly advantageous for diagnostic imaging, since they generate bright images, the renal toxicity of Gd-based contrast agents should not be ignored [18,19].…”
Section: Introductionmentioning
confidence: 99%